Islamic business ethics as a distribution solution in Indonesia - Latifah, Eny; Rifqi, Muhammad Afiqul; Antoni Julian (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2024)
This study aims to explore the application of Islamic business ethics principles in the field of distribution in Indonesia, focusing on how values such as justice, honesty, trustworthiness, and transparency can address various distribution challenges. Distribution is a crucial element in the economic chain; however, in Indonesia, geographical challenges, infrastructure disparities, and monopolistic practices often hinder efficiency and fairness in the delivery of goods and services. This study also seeks to provide strategic recommendations for creating more equitable and sustainable distribution systems aligned with Islamic values.The method employed in this study is library research with a descriptive qualitative approach. Data were gathered through literature analysis from books, scientific journals, articles, and other documents relevant to the topic of distribution from the perspective of Islamic business ethics. The analysis identified relevant Islamic ethical principles, such as the prohibition of hoarding (ihtikar), monopolies, and consumer exploitation, as well as how these principles can enhance efficiency and fairness in distribution.The findings indicate that the application of Islamic business ethics in distribution can serve as a strategic solution to address access disparities, foster transparency, and promote sustainability. These principles not only support inclusive economic growth but also strengthen consumer trust, thereby contributing to equitable welfare distribution across Indonesia.